Pharmacy and medical student interprofessional education placement week. (4th January 2022) - Jebara, Tesnime; Thomas, Ian; Cunningham, Scott; Rushworth, Gordon F.
Abstract: Background: Developing collaborative practice through interprofessional education (IPE) activities in undergraduate healthcare curricula is advocated by the World Health Organisation and the regulatory bodies for Medicine and Pharmacy within the UK. Approach: Our local faculty, comprising educators from within the Highland Pharmacy Education and Research Centre (HPERC) and Highland Medical Education Centre (HMEC), developed a 5‐day IPE placement for pharmacy and medical students on clinical placement within NHS Highland. Evaluation: We collected qualitative evaluation data using face‐to‐face focus group discussions with five pharmacy and four medical students (January 2020 cohort). Three key categories and multiple themes within each category were identified from participant narratives: Category 1, overall perception of experience—(themes: better than previous IPE experience; greater exposure to clinical pharmacy); Category 2, student interactions—(themes: learning with a buddy; understanding of interprofessional roles); Category 3, suggestions for improvement—(themes: choice of relevant clinical rotation and content; increase learning from clinical pharmacists; better orientation to placement). Overall, students valued their participation during this week and reported many benefits of learning with students from another profession. Students also highlighted suggestions to improve their learning experience. Implications: This evaluation has indicated students' support for embedding interprofessional placements into their curricula. Clinical educators should consider designing similar placements, while further work should focus on inclusion of higher student numbers and look to include a range of professions and practice settings.